Distribusi Keuntungan dan Risiko dalam Kemitraan Usaha Berbasis Syariah: Tinjauan Teoritis - roini, najiah fidda (Maliki Interdisciplinary Journal, 2025)
This study aims to examine the principles of profit distribution and risk sharing in business partnerships based on syirkah from the perspective of Islamic jurisprudence. In modern practice, there are many deviations from the basic principles of syirkah, such as fixed profit agreements and disproportionate loss sharing to capital. This study uses a library research method by reviewing classical literature, scientific journals, and official documents related to the topic of syirkah. The results of the study indicate that profits in syirkah can be shared based on agreement as long as there is willingness from both parties, while losses must be shared according to capital contribution. Deviations occur due to weak understanding of the principles of fiqh, lack of transparency, and weak sharia supervision. The solutions offered include strengthening sharia principles through understanding contracts, improving ethics and transparency, sharia financial literacy, good governance, and regulatory support. With this strengthening, the practice of syirkah is expected to run fairly and in accordance with Islamic values ​​in the context of a modern economy.